2013
DOI: 10.1139/cjfr-2012-0486
|View full text |Cite
|
Sign up to set email alerts
|

Long-term impact of a leaf miner outbreak on the performance of quaking aspen

Abstract: The aspen leaf miner, Phyllocnistis populiella Cham., has caused widespread and severe damage to aspen in the boreal forests of western North America for over a decade. We suppressed P. populiella on individual small aspen ramets using insecticide at two sites near Fairbanks, Alaska, annually for 7 years and compared plant performance with controls. Insecticide treatment successfully reduced leaf damage by P. populiella during most years and had little effect on herbivory by externally feeding invertebrates. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 39 publications
4
13
0
Order By: Relevance
“…). The reduction in C stores and radial growth associated with ALM has been noted previously (Wagner and Doak ). However, our results may be the first to demonstrate these effects on such a broad scale in interior Alaska.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…). The reduction in C stores and radial growth associated with ALM has been noted previously (Wagner and Doak ). However, our results may be the first to demonstrate these effects on such a broad scale in interior Alaska.…”
Section: Discussionsupporting
confidence: 79%
“…In addition to reduced C-uptake as a result of stomatal closure, mined leaves tend to abscise up to 4 weeks prior to undamaged leaves, which may further reduce water use, exacerbate the loss of C-uptake potential and further limit C resources available for defensive compounds and growth (Wagner et al 2008). The reduction in C stores and radial growth associated with ALM has been noted previously (Wagner and Doak 2013). However, our results may be the first to demonstrate these effects on such a broad scale in interior Alaska.…”
Section: Climatic and Biotic Drivers Of Aspen Growthmentioning
confidence: 82%
“…Surprisingly, we also found that gymnosperm species had negative growth associations related to increased July precipitation, perhaps due to an interaction with solar insolation. Lastly, we found significant increases in July VPD and insect‐driven mortality in aspen trees associated with a severe ongoing leaf miner outbreak (Doak & Wagner, ; Wagner & Doak, ; Wolken et al., ), and additional evidence that elevated leaf miner presence was associated with high midsummer evaporative demand (Tables S4a‐b), perhaps due to decreased aspen insect defenses resulting from unfavorable climate conditions (Allen, Breshears, & Mcdowell, ).…”
Section: Discussionmentioning
confidence: 60%
“…In central and western Canada, investigations using forest inventory measurements have attributed increases in tree mortality to increased competition resultant from rising atmospheric CO 2 , increased growing season length, and increased soil nutrient availability (Luo & Chen, 2015;Zhang et al, 2015). Sustained insect outbreaks in British Columbia (Kurz, Stinson, & Rampley, 2008) and interior Alaska (Doak & Wagner, 2015;Wagner & Doak, 2013) have also caused widespread species-specific tree mortality, likely amplified by an interaction between climate warming and insect life cycle and population dynamics (Raffa et al, 2008;Weed, Ayres, & Hicke, 2013).…”
mentioning
confidence: 99%
“…Leaf miner outbreaks have strong negative influences on plant development and aboveground biomass production: more basal sprout dieback, lower plant height, lower girth, smaller leave size, fewer leaf number, fewer petiole number, and fewer shoot number (Trumble et al, 1985;Norris, 1997;Kozlov, 2005;Wagner & Doak, 2013). Leaf-mining injury could cause severe loss of the total leaf area (Hileman & Lieto, 1981;Peña et al, 2000;Nardini et al, 2004).…”
Section: Impacts On Plant Growth and Productionmentioning
confidence: 99%